RESTRUKTURISASI KEBIJAKAN LUAR NEGERI FILIPINA: UPAYA PRESIDEN RODRIGO DUTERTE UNTUK MENGAKHIRI DEPENDENSI KE AMERIKA SERIKAT - Dzulfiqar Fathur Rahman; Mohamad Rosyidin (Journal of International Relations Diponegoro, 2019)
Under President Rodrigo Duterte, Philippines pursues the so-called independent foreign policy that’s associated with the decline in its special relationship with the United States. By conducting a case study based on the theory of foreign policy restructuring, this research seeks to explain why the Philippines undertake foreign policy change in a dramatic and fundamental manner. Following Holsti, this research argues that the Philippines’ foreign policy restructuring is a response to non-military threat. The United States’ interference in Duterte’s anti-drug campaign and South China Sea (or SCS) policy constitutes such threat. This research finds that non-military threat led the Philippines to restructure its foreign policy that undermines its bilateral relations with the United States, while improving its relations with non-traditional state partners such as China and Russia.